Windows 2000 active directory - Craft, Melissa (Rockland, Mass. : Syngress Media ; London : International Thomson, 2001)
Updated coverage of the most confusing Windows 2000 component in this new edition of a Syngress bestseller. Active Directory Services dramatically changes the way IT professionals design, plan, configure and administer their Windows NT networks. The primary benefits of Active Directory Services are its extensibility, scalability, and ease of management as compared to prior generations of Windows NT. Systems Engineers will probably spend much of their time over the next several years planning for and deploying Active Directory Services in many different environments. Windows 2000 Active Directory, Second Edition gives IT professionals a head start; it provides updated coverage of everything they will need to succeed. Many Windows 2000 administrators are struggling with Active Directory and need a comprehensive book on the subject The first completely updated book on Active Directory to hit the market.
Keywords: Microsoft Windows (Computer file).; Electronic books